Nursing care of a patient with ankylosing spondylitis in the context of Dorothea Orem’s theory: a case report - Augustyn, Anna; Kliś-Kalinowska, Anna; Wojcieszek, Agata; Kurowska, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2026)
Ankylosing spondylitis (Bechterew’s disease) is a difficult-to-diagnose chronic inflammatory disease that primarily affects the spine and sacroiliac joints. Advanced disease requires holistic care to reduce pain and the patient’s other symptoms. The aim of the study was to assess the needs of a patient diagnosed with ankylosing spondylitis and her self-care capacity based on Dorothy Orem’s theory. The research was conducted using the case study method. The article presents the patient’s health problems and develops a nursing care plan using the ICNP terminology. The patient experienced self-care deficits, chronic pain, depressed mood, and constipation. An appropriately designed nursing care plan helped to reduce some of the patient’s problems, which led to a better quality of life.